Protected Sex with Paid Sexual Partner among Married Men in Indonesia - Putra, I Gusti Ngurah Edi (GHMJ (Global Health Management Journal), 2019)
Background: Married men who are male clients of sex workers play an important role as “bridge population” of HIV infection from the concentrated epidemic population to the general population. This study aimed to investigate the protected sex with last paid sexual partner among currently married men in Indonesia.  Method: A nationally representative population-based survey, 2012 Indonesia Demographic and Health Survey (IDHS) which covered 33 provinces in Indonesia was applied in this study. Out of 9,306 currently married men, 510 records of married men who reported for ever paying someone for having sex were eligible for this study. A dependent variable was protected sex (i.e. condom use) at last sex with a paid sexual partner whilst independent variables consisted of socio-demographic factors, spousal communication on HIV prevention, knowledge of HIV prevention, and attitude of condom use. Binary logistic regression was applied for bivariate and multivariate analysis.Results: Prevalence of condom use with a paid sexual partner at last sex among currently married men was 27.86% [95%CI=23.89-32.20]. Based on multivariate analysis, married men were less likely to use a condom with a paid sexual partner if they aged ≥ 40 years old (OR=0.48; 95%CI=0.30-0.76) versus those aged < 40 years old and worked in some sectors: clerical (OR=0.22; 95%CI=0.08-0.61), sales (OR=0.40; 95%CI=0.17-0.95), agricultural/self-employed (0.32; 95%CI=0.13-0.75), skilled manual (OR=0.38; 95%CI=0.18-0.79) compared to those working in professional/technical/engineering sectors. However, those who were from poorer (OR=2.28; 95%CI=1.08-4.82) and richest household (OR=3.08; 95%CI=1.32-7.20) were more likely to perform protected sex compared to the poorest ones. In addition, the likelihood of protected sex also increased when married men had spousal communication on HIV prevention (OR=1.84;95%CI=1.17-2.90), knew that using condoms can reduce HIV infection (OR=2.15; 95%CI=1.14-4.08) and had a positive attitude of using condoms can protect against diseases (OR=3.05; 95%CI=1.14-8.16). Conclusion: Interventional approaches for increasing protected sex among married men as clients of sex workers should be integrated with existing HIV program among other key affected populations (e.g., FSWs) at sex workers’ workplaces setting through providing HIV-related information, ensuring uninterrupted stocks of condoms, and enforcing condom use regulation.